Development of the South Java Coastal Crossroads (Case Study of the Legundi-Planjan Road Section, Gunungkidul Regency, Special Region of Yogyakarta Province) - Puspito, Bambang Anjar (Universitas Ibn Khaldun Bogor, 2025)
The performance of the Legundi – Planjan (LOT-4) road, Gunungkidul Regency, Yogyakarta Special Region Province, is a study conducted in one of the sections on the Southern Java Cross Coastal Line (PANSELA). The purpose of the research is to conduct: Traffic Volume Counting, Traffic Time Speed Calculations, Potential Analysis and discussion of Tourism and Fisheries, Vehicle Operating Cost Calculations, Value of Travel Calculations Travel Time Saving), Accident Cost Calculation.The research method is carried out with the stages of a Traffic Volume Enumeration Survey to determine the amount of traffic volume that passes through the location of the observation point manually according to the grouping of vehicle types within a certain time period. This survey was conducted by counting the number of motorized vehicles by vehicle type group in a period of 15 minutes for 16 hours, to determine the characteristics of traffic flow. Travel speed survey is to obtain information on the average travel speed of vehicles that pass certain roads at predetermined locations, the survey is carried out using the moving observer method. The data obtained is used to calculate vehicle operating costs classified into fixed costs (fixed costs) and variable costs (variable costs). Fixed costs are costs that must be paid even if the vehicle is not used, the amount is constant. While the variable costs of using the vehicle according to need. Calculations as developed by the Japanese PCI Consultants (Pacific Consultants Indonesia). The Travel time value observes an increase in travel speed and shorter roads, an increased time value means a travel time savings. Calculation of the cost of motor vehicle accidents is divided into: Accidents that cause fatalities, injuries without casualties and property damage. By comparing the calculation of accident costs with the upper control limit and upper control limit to determine the accident-prone area (black side). The results obtained are (Traffic Counting = 615 smp/hour). , (Travel Time Speed=38.36 km/hour), (Vehicle Operating Cost, Passenger Car=Rp.4.837,26; Truck=Rp.6.037.81; Bus=Rp.9.322.38), (Value of Travel Time Saving= for an average speed of 38.36km/hour=Rp.100.10 ), (Equivalent Accident Number=EAN in Panggang sub-district in 2018=198 above the Upper Control limit /UCL=164 and BKA(Upper Control Limit=197).